2016
DOI: 10.18353/crustacea.45.0_15
|View full text |Cite
|
Sign up to set email alerts
|

A review of the <i>Chaenostoma boscii</i> species-complex (Decapoda: Brachyura: Macrophthalmidae) from the Indo-West Pacific

Abstract: Abstract. The sentinel crabs, Chaenostoma orientale Stimpson, 1858, and C. crassimanus Stimpson, 1858, were both described from the Ryukyu Islands, Japan, and have both been long considered junior synonyms of C. boscii (Audouin, 1826). After examining specimens of the C. boscii species-complex from East Africa, the Malay Peninsula, Indonesia, New Caledonia, Papua New Guinea, the Philippines, Taiwan, and the Ryukyus, we now consider both C. crassimanus and C. orientale to be valid species, and C. lisae (Poupin … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 28 publications
1
4
0
Order By: Relevance
“…The morphology of the specimens (Fig. 1) examined herein matches the description and illustrations given by Naderloo and Türkay (2011) and Teng et al (2016), but varied slightly in following characters: lateral margins of third somite of male abdomen are strongly curved (Fig. 1d) (vs. almost straight in holotype of C. sinupersici), operculum of female gonopore (Fig.1e) is larger in size reaching median part of gonopore opening (vs. smaller operculum not reaching median part of gonopore opening in paratype female of C. sinupersici).…”
Section: Introductionsupporting
confidence: 73%
See 3 more Smart Citations
“…The morphology of the specimens (Fig. 1) examined herein matches the description and illustrations given by Naderloo and Türkay (2011) and Teng et al (2016), but varied slightly in following characters: lateral margins of third somite of male abdomen are strongly curved (Fig. 1d) (vs. almost straight in holotype of C. sinupersici), operculum of female gonopore (Fig.1e) is larger in size reaching median part of gonopore opening (vs. smaller operculum not reaching median part of gonopore opening in paratype female of C. sinupersici).…”
Section: Introductionsupporting
confidence: 73%
“…Another species, Chaenostoma lisae (Poupin & Bouchard, 2010) is now considered as junior synonym of C. crassimanus (Shih et al, 2015;Teng et al, 2016). Chaenostoma sinuspersici was described from Persian Gulf and has a widespread distribution in Indo-West Pacifi c (Naderloo and Türkay, 2011;Teng et al, 2016). In the present study, C. sinuspersici is reported fi rst time from Indian waters.…”
Section: Introductionmentioning
confidence: 50%
See 2 more Smart Citations
“…Türkay 2011, Teng et al 2016) and M. boscii and allied taxa were transferred to the genus Chaenostoma. Teng et al (2016) showed that two species, C. crassimanus Stimpson, 1858 and C. orientale occur in the north-western Pacific, including Japan, with true C. boscii restricted to the western Indian Ocean. At the studied site, specimens of C. orientale have been collected and, thus, it is reasonable to consider that it was the eDNA of C. orientale that was detected and that the GenBank sequence identified as "Macrophthalmus" boscii has been misidentified.…”
Section: Taxa Detected From Edna Metabarcodingmentioning
confidence: 99%